Ultra-narrow linewidth single longitudinal mode Brillouin fiber ring laser using highly nonlinear fiber - Ahmad, Harith; Razak, Nor Farhah; Zulkifli, Mohd Zamani; Muhammad, Farah Diana; Munajat, Yusof; Harun, Sulaiman Wadi (Institute of Physics Publishing, 2013)
In this letter, we demonstrate a single longitudinal mode (SLM) Brillouin fiber laser by using highly nonlinear fiber (HNLF) as the nonlinear medium in which the stimulated Brillouin scattering effect takes place. The first Stokes line is generated at a threshold power of 18 dBm with a wavelength shift 0.08 nm from the Brillouin pump. The signal-to-noise ratio of the first Stokes line is measured to be ∼58 dB. To the best of the authors’ knowledge, this is the first report of a 0.7 kHz ultra-narrow linewidth of an SLM Brillouin fiber laser, using HNLF as the nonlinear medium, which features a simple cavity configuration.